Natural Diversity in Total Phenol, Flavonoids, Antioxidant Properties, and Essential Oil Composition of Iranian Populations of Myrtus communis L. - Reza Yarahmadi; Hasan Mumivand; Abdollah Ehtesham Nia; Mohamad Reza Raji; Sergio Argento (Plants)
Myrtus communis L. (Myrtaceae), widely valued for its aromatic leaves and essential oil, plays a significant role in traditional medicine and modern phytotherapy. The variability in its essential oil composition and bioactive compounds across different populations underscores its potential for novel therapeutic discoveries and agricultural utilization. This study aimed to evaluate the phytochemical diversity of 12 selected Iranian M. communis populations in their natural habitats. Leaf samples were collected in 2023 from these native habitats to assess various parameters, including phenolic compounds (total phenols and total flavonoids), antioxidant capacity, essential oil content, and essential oil composition. The results indicated significant variations in phenolic content and antioxidant capacity across the populations. The Khoraman population, used as a control, exhibited the highest levels of total phenols and flavonoids, followed by the Sar-sarab and Yazd populations, while the Poldokhtar and Kermanshah populations showed the lowest levels. Additionally, the Poldokhtar and Hormozgan populations demonstrated the highest antioxidant capacities. Essential oil content ranged from 0.480 to 1.478%, with the Khoraman and Padeghan populations having the highest percentages of 1.631 and 1.478%, respectively. GC/MS analysis identified 29 distinct compounds in the essential oils, with major components including 1,8-cineole (22.34 to 45.66%), α-pinene (19.25 to 35.96%), linalool (7.79 to 18.76%), and α-terpineol (5.26 to 9.17%). The myrtle populations were categorized into four groups: (1) Khoraman; (2) Shiraz and Yazd; (3) Ilam, Sar-sarab, Poldokhtar, and Padeghan; and (4) Khuzestan, Kerman, Kermanshah, Kohgiluyeh–Boyer–Ahmad, and Hormozgan. Principal Component Analysis (PCA) corroborated the cluster analysis results, as populations within each group displayed similar distributions in the biplot.